Membedah Masalah Kemiskinan Ekonomi di Indonesia dari Perspektif Karl Marx tentang Agama sebagai Produks Alienasi - I Made Priana (Sekolah Tinggi Theologia Nazarene Indonesia, 2017)
This article tries to explore the economic poverty in Indonesia from Karl Marx’s perspective that religion is the product of alienation. Critical insight from Karl Marx that religion tends to give comfort to the suffering people by showing them about the happiness in the world after, and not to empower the suffering people to struggle and to overcome the suffering by working hard and working smart, is seemingly constructive. It is said so, since religion has spiritual and social dimention. Even, religion has function to transform that the world where we live now become the heavenly world. Religion must teach people not to escape from difficulty but to overcome it for a better life in this world. As religious people we not have to dream that we have wings to fly seeking other world. Istead, we have to pray that we present the heavenly world in this world by doing that we are for the poor that they might have a better life.